Treatment of Severe Steroid-Refractory Acute-Graft-vs.-Host Disease With Mesenchymal Stem Cells–Single Center Experience - Česen Mazič, Maja; Girandon, Lenart; Kneževič, Miomir; Avčin, Simona L.; Jazbec, Janez (Frontiers in Bioengineering and Biotechnology, 2018)
The most effective treatment of steroid refractory acute graft vs. host disease (aGvHD) is not yet established and mesenchymal stem cells (MSC) appear to be a promising therapy for the condition. We report single center case series of three patients, who underwent allogeneic hematopoietic cell transplantation and later developed steroid refractory graft-vs.-host disease, treated with MSC infusions. Two patients achieved complete remission and one patient partial remission of skin and/or gastrointestinal aGvHD. We demonstrated application of MSC for treatment of severe steroid refractory aGvHD is feasible in clinical practice. Detailed description of patient's features and MSC production protocol is crucial for future comparison on efficacy and safety of cell-based therapies. However, for any substantial conclusions regarding efficacy of MSC higher patient numbers will be required.